Protein S Tokushima: An Abnormal Protein S Found in a Japanese Family with Thrombosis - Shigekiyo, T; Uno, Y; Kawauchi, S; Saito, S; Hondo, H; Nishioka, J; Hayashi, T; Suzuki, K (Thrombosis and Haemostasis, 1993)
An abnormal protein S (PS) was found in a Japanese family with a high incidence of thrombosis. The proband is a woman who was born in Tokushima Prefecture. She had superior sagittal sinus thrombosis, thrombophlebitis of the left leg, and thrombosis of the placenta. She had a normal plasma level of free PS antigen but decreased PS activity. Her mother and aunt also had thrombophlebitis of the leg, and together with four other family members also showed a normal level but decreased activity of PS. This suggests that hereditary dysfunction of PS is inherited in this family as an autosomal dominant trait. The proband’s PS appears to have a slightly higher molecular weight than normal PS both in the intact and modified form, suggesting that it has a molecular defect on the carboxyl-terminal side of the thrombin-sensitive site. This abnormal PS with apparently unique characteristics was named PS Tokushima.